Connected Objects in Information Systems & - ABALLO, ONYONKITONON THEOPHILE (My University, 2020)
The Internet of Things connects technical systems and sometimes also mechanical parts, electronic or even raw materials, with the web, via standardized communication interfaces. This opens up the ability to monitor and control devices and feeds for authorized users, as well as providing access to malicious people. Connected objects are also increasingly used for industrial applications. We are now talking about Industry with connected and intelligent factories to gain competitiveness. But these devices present intrinsic vulnerabilities and risks related to the new uses made possible thanks to an almost continuous connectivity to the Internet. There are actually very few areas of empirical testing currently. While waiting for a greater technological maturity of the Internet of Things, using supervision provides complete visibility of the entire network, which can greatly contribute to its security. The purpose of this article is to study objects connected to information systems..
Keywords: Internet of Things · Risks · Vulnerabilities